Circular Economy in the EU- Correlation between the Tertiary Education Attainment and Recycling Rate of Municipal Waste - GEORGE-CORNEL DUMITRESCU (Global Economic Observer)
The new coronavirus crisis revealed the weaknesses of our linear economic model, particularly the overdependence on long supply chains and specific countries. In this new context, the circular economy and the principles of reducing, reusing, and recycling are getting new meanings, forcing the decision-makers into adopting new ways of achieving economic sustainability. In our paper, we investigate if, in the EU, there is any correlation between the tertiary education attainment and the recycling rate of municipal waste. We aim to emphasize that higher education is essential in the transition towards the circular economy. To this end, we used the database of Eurostat and several statistical tools.